A systematic review and meta-analysis of the Endometriosis and Mental-Health Sequelae; The ELEMI Project - Delanerolle, G; Ramakrishnan, R; Hapangama, D; Zeng, Y; Shetty, A; Elneil, S; Chong, S; Hirsch, M; Oyewole, M; Phiri, P; Elliot, K; Kothari, T; et al. (SAGE Publications, 2021)
Background: It is important to evaluate sequalae for complex chronic health conditions such as endometriosis and mental health disorders. Endometriosis impacts 1 in 10 women. Mental health outcomes can be a primary determinant in many physical health conditions although this is an area not well researched particularly in women’s health. This has been problematic for endometriosis patients in particular, who report mental health issues as well as other key comorbidities such as chronic pelvic pain and infertility. This could be partly due to the complexities associated with comprehensively exploring overlaps between physical and mental health disorders in the presence of multiple comorbidities and their potential mechanistic relationship.